Ruang Lingkup Desentralisasi Manajemen Pendidikan - Dianika Putri Aulia; Anne Effane (Universitas Djuanda, 2023)
Decentralization of education management is essentially the authority of the central government to provide full abundance to regional governments, to manage their own households in all matters. The affairs in question are about all matters related to education management. All matters of abundance are given to regional autonomy, unless there are certain affairs which are still part of government affairs, or the right of the government itself to manage everything. The scope of education management is one that is related to various parties and is multidisciplinary. These multidisciplinary disciplines include management of education and educational staff, in addition to student management and curriculum management, financing management, facilities and infrastructure management, school management, principal management and community relations management. Everything is related to one another so that the decentralization of education management is implemented properly. This scope is also still divided into several sections, among which there is scope according to work area. Where, within this scope management is divided into several classes including management of the whole country, management of one province, management of one work unit and class management. Next, there is scope according to cultivated objects, including student management, education personnel management, management of facilities and infrastructure, administrative management, and financing management, and finally there is scope related to activity functions where this relates to planning, organizing, directing , coordinate, communicate, and monitor or evaluate. The process of processing the scope in the decentralization of education certainly has many obstacles. To see the success of the scope of decentralization of education management, this research seeks quantitative data, which collects data, analyzes and provides conclusions about the success of the scope of decentralization of education.